Gempaq Raya 22 Lagu kenangan Raya (Selangor : EMI (Malaysia) Sdn. Bhd., 1999)
Mengandungi 22 koleksi lagu hari raya
Title from container
Penyanyi: Harakat Madani, Fauziah Latiff, Sharifah Aini, Saloma, P. Ramlee, Sudirman, Hail Amir & Uji Rashid, Fazidah Joned, Sanisah Huri, Noorkumalasari, Uji Rashid, Elite, Aishah, Rafeah Buang, Krisya, Ahmad Jais, Junainah, D.J. Davem Sheila Majid, Rahimah Rahim, Black Dog Bone, Sharifah Aini, Rabbani, Harakat Madani
Keywords: Song, Malay; Collections